Program Adiwiyata dalam Pembangunan Lingkungan Dusun dan Pembentukan Karakter Siswa untuk Peduli terhadap Lingkungan Sekolah - Shelly Rasyta Ananda; Anindya Putri; Nabila Mauldy Erwanto; Nessa Dila Arifqi; Citrawati Nur Feby Dinata; Muhammad Yusuf Firdaus; Muhammad Nurul Anam; Muhammad Rifki Ulul Albab; Bintang Tri Aji Pamungkas (Lembaga Pengembangan Kinerja Dosen, 2024)
The Community Service Program (KKN) implemented by universities in district or city areas is expected to provide change, sustainable development and have benefits for the community. In Group 2 KKN in Ringinanom Village, Tempuran District, Magelang Regency, several quality work programs have been implemented, one of which is the adiwiyata program which can be used to form and increase awareness of the people of Bedilan Hamlet and students of MI Al-Islam Ringinanom about the importance of protecting the surrounding environment. hamlets and school environments. The Adiwiyata program is carried out using a Participatory Rural Appraisal (PRA) approach. This service was carried out to overcome problems in the environment around the hamlet and school which looked dirty and unkempt, so that the service carried out by Ringinanom Village KKN Group 2 has provided a solution to overcome existing problems through the adiwiyata program and activities that have been implemented. The Adiwiyata program that has been implemented has provided results such as making the environment of Bedilan Hamlet and MI Al-Islam Ringinanom cleaner and appearing free of plastic waste strewn on the side of the road, as well as gutters full of wild plants now looking clean so they will not cause water blockages when it rains. The construction of gates and road signs which initially did not exist in Bedilan Hamlet have now been neatly installed as a manifestation of the construction of facilities/infrastructure carried out by Group 2 of the Ringinanom Village KKN. Based on the activities that have been carried out at MI Al-Islam Ringinanom and with some knowledge about the importance of protecting and preserving the environment, students are now more active in carrying out cleanliness pickets so that the activities with Group 2 of the Ringinanom Village KKN make students accustomed to keeping the classroom and school environment clean